HUBUNGAN PENGETAHUAN DENGAN DUKUNGAN KELUARGA TENTANG GIZI PADA LANSIA DI KELURAHAN PULAU SIMARDAN TANJUNG BALAI TAHUN 2020 - MENI FUZI ASTUTI TANJUNG TANJUNG (Universitas Prima Indonesia, 2022)
According to WHO (Word Health Organization) Naturally, the elderly will experience the aging process so that this process will reduce physical, psychological and social conditions which result in health problems in old age, for lifestyles in old age can also be influenced by food and drink. drinks consumed, namely eating that is not contained in the nutritional value, and consuming alcoholic beverages, so that this kind of lifestyle can also affect the nutritional status of the elderly. This study aims to make the elderly understand the nutrients needed by the body. This research is descriptive in nature using primary data, namely data obtained from direct field observations using a previously designed questionnaire to determine the relationship between knowledge and family support about nutrition in the elderly in Pulau Simardan Village, Tanjung Balai City in 2020, the population and sample in this study amounted to 38 respondents and based on the results of the study, respondents who had good knowledge with good support categories were 7 people (58.3%), and respondents who were well informed with less support were 5 people (41.7%), the results showed a significant relationship between knowledge Elderly with family support for nutrition in the elderly with a value of p=0.002 0.05 (p<0.05). From this research, it is hoped that every elderly will seek and explore more information in order to increase knowledge about nutrition in the elderly